Consideraç\~oes distributivas em análise custo-benefício - Matheus Stivali; Taíse Fátima Mattei (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– This work assesses the possibilities of including distributive considerations into cost-benefit analysis (CBA), it summarizes the favourable and contrary arguments existing in the literature, as well how it can be done. A survey is also carried out on how the topic is treated by agencies and organizations that practice CBA to evaluate investment projects. The evaluations of the theoretical lines and the practice adopted in several agencies indicate that the best choice to combine economic efficiency analysis with distributive concerns for the evaluation of projects is achieved through the adoption of an hybrid criteria. This would involve the execution of the traditional CBA, evaluating aspects of efficiency, together with an analysis of the project's distributive impact, that could be done through a cost and benefit accounting matrix or by calculating indicators of impact on poverty and inequality. The joint elaboration of the two analyses would guarantee the consistency of these regarding the identified costs and benefits and also regarding the affected population.
10419/284906
Keywords: D61; D63; D31; O15; 330; cost-benefit analysis; distributive impact; income distribution; allocative efficiency; distributive weights